2011
DOI: 10.1002/rcm.4908
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric stereoisomeric differentiation between α‐ and β‐ascorbic acid 2‐O‐glucosides. Experimental and density functional theory study

Abstract: L-Ascorbic acid and two distinct anomers, namely the α-D-glucopyranosyl and β-D-glucopyranosyl-(1→2)-L-ascorbic acid (stereoisomers), were studied within the scope of collision-induced dissociation (CID) experiments, performed by linear ion acceleration and collision with argon atoms inside a hexapole quadrupole hexapole ion beam guide, which is coupled to an ion cyclotron resonance (ICR) cell with a 12 Tesla magnet for high-resolution measurements. Loss of C(2)H(4)O(2) neutral from the [M-H](-) anion of L-asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Moreover, the MS/MS spectrum showed that with the collision energy of 35.0 eV, the precursor anion [M‐H] − ( m / z 337.0724) was collided to 2 fragment ions, including the parent anion m / z 337.0712 and another fragment ion m / z 277.0517 (Figure B). It was considered consistent with the loss of C‐5 and C‐6 from the ascorbic acid portion of the molecule (Figure C), by which could be tentatively identified as 2‐ O ‐β‐ d ‐glucopyranosyl‐ l ‐ascorbic acid (AA‐2βG) according to the literatures (Toyoda‐Ono and others ; Tai and Gohda ; Kanawati and others ). Furthermore, Hancock and others () revealed that the maximum wavelengths of targeted compound identified by ESI‐Q‐TOF‐MS/MS were 235 and 259 nm, which was homologous to HPTLC‐UV results (Figure A) and could further verify the identified compound.…”
Section: Resultssupporting
confidence: 68%
“…Moreover, the MS/MS spectrum showed that with the collision energy of 35.0 eV, the precursor anion [M‐H] − ( m / z 337.0724) was collided to 2 fragment ions, including the parent anion m / z 337.0712 and another fragment ion m / z 277.0517 (Figure B). It was considered consistent with the loss of C‐5 and C‐6 from the ascorbic acid portion of the molecule (Figure C), by which could be tentatively identified as 2‐ O ‐β‐ d ‐glucopyranosyl‐ l ‐ascorbic acid (AA‐2βG) according to the literatures (Toyoda‐Ono and others ; Tai and Gohda ; Kanawati and others ). Furthermore, Hancock and others () revealed that the maximum wavelengths of targeted compound identified by ESI‐Q‐TOF‐MS/MS were 235 and 259 nm, which was homologous to HPTLC‐UV results (Figure A) and could further verify the identified compound.…”
Section: Resultssupporting
confidence: 68%
“…The 146.058 [M‐H] − cleaved‐off fragment has the predicted elemental composition of C 6 H 10 O 4 (0.7 ppm) and was not detected in the analysis. The fragmentation of this group probably occurred as a neutral loss accompanied by a proton shift from the conjugated group to the glutathione moiety, which induces an intramolecular rearrangement of the group (Kanawati et al ., ). Thus, the original conjugated group in the neutral GS conjugate has a sum formula of C 6 H 11 O 4 .…”
Section: Resultsmentioning
confidence: 97%
“…HILIC and RP LC-MS were performed on the crude lipid extracts with an ACQUITY UPLC® (Waters, Milford, USA) connected to an UHR QqToF mass spectrometer (maXis™, Bruker, Bremen, Germany). Molecules of interest were further analyzed at ultra-high resolution (<300,000 at m/z 300) and fragmented in negative electrospray ionization mode to identify the fatty acid side chains with an Ion Cyclotron Resonance Fourier Transform Mass Spectrometer (ICR-FT/MS, solariX™, Bruker Daltonics GmbH, Bremen, Germany) [45]. See Figure S1 and Movie S1 for further details and controls.…”
Section: Methodsmentioning
confidence: 99%